1997
DOI: 10.1111/j.1399-6576.1997.tb04868.x
|View full text |Cite
|
Sign up to set email alerts
|

Contradictory effects of dopamine at 32°C in pigs anesthetized with ketamine

Abstract: Dopamine increased CO and MAP in normothermia but not at 32 degrees C, where there was even a significant reduction of MAP in this porcine model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The physiologic effects of pharmacological vasodilatation might also be more pronounced in hypothermia, since the possibility for a compensatory tachycardia is reduced. We think these aspects might explain the earlier reported paradoxic decrease in cardiac output after dopamine at 32 °C (2).…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…The physiologic effects of pharmacological vasodilatation might also be more pronounced in hypothermia, since the possibility for a compensatory tachycardia is reduced. We think these aspects might explain the earlier reported paradoxic decrease in cardiac output after dopamine at 32 °C (2).…”
Section: Discussionmentioning
confidence: 65%
“…A study in sheep (4) showed a decrease in dP/dt, MAP and CO with low doses of dopamine in hypothermia, whereas higher doses in hypothermia and all doses in normothermia increased these parameters. In a study using small pigs, we also found that administration of dopamine at 32 °C caused a substantial decrease in blood pressure and no increase in cardiac output, although the heart rate increased (2). However, it seems likely that a relatively high baseline heart rate after cooling in this study may have led to a tachycardia during dopamine infusion that influenced ventricular filling in hypothermia (16).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Likewise, positive inotropic effects of dopamine were found in pigs core cooled to 30 °C [57]. However, in pigs surface cooled to 32 °C [62] and 25 °C [63] dopamine did not elevate CO. In the latter study, which was conducted in our lab [63], dopamine infusion at 25 °C gave a four-fold increase in plasma concentration compared to normothermia.…”
Section: Methodsmentioning
confidence: 99%